High glucose distinctively regulates Ca2+ influx in cytotoxic T lymphocytes upon target recognition and thapsigargin stimulation. Issue 12 (18th August 2020) - Zou, Huajiao; Yang, Wenjuan; Schwär, Gertrud; Zhao, Renping; Alansary, Dalia; Yin, Deling; Schwarz, Eva C.; Niemeyer, Barbara A.; Qu, Bin
Abstract : In CTLs: High glucose‐culture enhances thapsigargin‐induced SOCE but decreases target recognition‐induced Ca 2+ influx. High glucose‐culture regulates expression of ORAIs and STIMs without affecting glucose uptake. More high glucose‐cultured CTLs are prone to necrosis after execution of killing.